ANALYTICAL APPROACHES IN UNVEILING THE COMPATIBILITY OF COLLAGENASE WITH ADDITIVES IN VIEW OF ITS COLLOIDAL DELIVERY - Landge Anil Vijay; Krishnamoorthy Kannan (Journal of the Chilean Chemical Society, 2019)
The core objective of present work was to investigate the chemical interactions of selected additives with therapeutic enzyme Collagenase (COLG) and determination of its compatibility for futuristic colloidal formulation. Initially, solubility of COLG with additives was determined and emulsification efficiency of surfactants was examined. FTIR spectra of COLG with its binary blends were compared. Non-denaturing SDS-PAGE and Circular Dichroism (CD) used to investigate primary and secondary structure of enzyme in binary mixture. Finally, the control and accelerated studies was performed by spectroscopy.